Interleukin 12 receptor deficiency in a child with recurrent bronchopneumonia and very high IgE levels - Palamaro Loredana; Giardino Giuliana; Santamaria Francesca; Romano Rosa; Fusco Anna; Montella Silvia; Salerno Mariacarolina; Ursini Matilde; Pignata Claudio (BMC, 2012)
Abstract Interleukin-12 (IL-12) is involved in cellular immune responses against intracellular pathogens by promoting the generation of T naive in T helper 1 (Th1) cells and by increasing interferon-gamma (IFN-gamma) production from T and natural killer (NK) cells. A defective induction of a Th1 response may lead to a higher risk of infections, and, in particular, infections due to typical and atypical Mycobacteria. We report on the case of a girl with suffering from recurrent bronchopneumonia associated with very high serum IgE levels, who exhibited a profound impairment of the Th1 generation associated with a novel mutation in the exon 5 of the IL-12R β1 gene (R156H). Our data suggest that in children with severe and recurrent infections, even in the absence of a mycobacterial infection, functional and/or genetic alterations of the molecular mechanisms governing Th1/Th2 homeostasis might be responsible for an atypical immunodeficiency and, therefore, should be investigated in these patients.